Analyzing The Impact Of Reward And Punishment Strategies, Internal Public Relations, And Digital Marketing On Company Profitability - Sri Utami Nurhasanah; Sarah Fitriyani (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2023)
This study aims to investigate the influence of reward & punishment strategies, internal public relations, and digital marketing on company profitability. Employing a qualitative research design, the study utilizes purposive sampling to select participants from various industries, aiming for diverse perspectives. Data analysis involves thematic coding to identify patterns and themes emerging from interviews and textual analysis of relevant documents. Preliminary findings suggest that effective implementation of reward & punishment strategies, coupled with robust internal public relations and adept digital marketing, significantly impacts company profitability. The study underscores the importance of cohesive internal communication and strategic digital marketing efforts in enhancing organizational performance and financial outcomes.